Exploring the Moderating Role of Work Motivation on the Impact of Academic Supervision and Workplace Culture on Teacher Professionalism - Sunarsih, Sri; Egar, Ngasbun N; Abdullah, Ghufron G. (JURNAL AL-TANZIM, 2025)
Teacher professionalism is paramount for adapting to today’s evolving educational demands and ensuring quality student outcomes. This research is crucial for understanding how to effectively enhance it. The research specifically aimed to analyze how work motivation moderates the relationship between academic supervision, workplace culture, and teacher professionalism. The research is a quantitative study employing a correlational design. The population consists of 153 elementary school teachers. A sample of 110 teachers was selected through a proportional random sampling technique. Data was collected using a questionnaire developed with a 4-point Likert scale. The data analysis was performed using Moderated Regression Analysis (MRA). The research concluded that work motivation moderates the effect of academic supervision and workplace culture on teachers’ professional development. This finding suggests that a teacher’s level of motivation influences the effectiveness of academic supervision and workplace culture in promoting professionalism. Thus, for genuine improvements in professionalism, efforts must strategically focus on both strengthening supervisory practices and culture, as well as cultivating high levels of teacher motivation.